Situación de salud en los pobladores del caserío Los Ángeles en el distrito de Santa Cruz de Chuca – Santiago de Chuco 2010 - Chávez Delgado, Ghisel Selky (2010)
A descriptive study was cross sectional, in order to determine the current status of health of the inhabitants of the hamlet of Los Angeles in the Santa Cruz district of Pachuca in the province of Santiago de Chuco - Region La Libertad. The study was conducted during the months of February and May 2010. 81 families were surveyed house to house, also conducted interviews with village and district authorities, through surveys of the size variables as biological, economic, ecological, conscience and conduct, being a remote and rugged terrain that limits access to health facilities to meet health priorities. Additionally, we found a predominantly young population (59.4%) with low educational attainment across the population, corresponding mostly to incomplete primary (48.10%). Nutritional status is poor with children who have low physical, presence of malnutrition (58%). The main industry is agriculture. According to the morbidity reported by the health post for the population Cochapampa hamlet of Los Angeles, is presented respiratory diseases (50%), followed by acute diarrheal diseases (5.88%) and intestinal infections (2.9%) and finally parasitic diseases (14.7%) prevalence. But the presence of diseases empirical population uses medicinal plants and generally do not go to a health post, by the inaccessibility problems mainly. We conclude that the current state of health of the residents of the hamlet of Los Angeles is poor